Pemanfaatan Limbah Rumah Tangga Sebagai Pupuk Organik Cair Dan Penggunaan Benih Baru Varietas Lokal Di Desa Sokaan - Zuhro, Mimik Umi; Su’ud, Moch.; Dwicaksono, Pramuditya; Candra, Muhammad Fajar Sodiki (Universitas Mataram, 2023)
Household waste, which is formed from daily activities in the household, contains various types of materials that have lost value or are considered useless by household residents. This type of waste can generally be divided into two forms, namely solid and liquid waste. One of the innovative approaches implemented is the use of household waste as a basic ingredient in the production of liquid organic fertilizer (POC). This brings dual benefits, namely reducing the negative impact of environmental pollution while increasing the fertility of agricultural land. POC, which is an abbreviation for liquid organic fertilizer, is a solution produced through a natural fermentation process using raw materials such as plant residues, animal waste, or even human waste. In this context, POC is described as a sustainable and environmentally sound option in the world of agriculture. The advantage of POC lies in its existence in liquid form, which has appeal to farmers who care about the environment and human health. In addition, POC contains various microorganisms which play an important role in accelerating plant growth and development. Selection of local plant varieties that have been adapted to environmental conditions in Sokaan Village is also an important part of this service. This step aims to strengthen the sustainability of local agriculture, increase crop productivity and reduce dependence on imported varieties. Thus, this service activity has significant implications in efforts to support sustainable and environmentally friendly agriculture at the local level.